Strategi Santri Menjaga Keseimbangan Antara Hafalan Al-Qur’an Dan Pelajaran Umum Di Madrasah Aliyah Tahfizil Qur’an Medan - Manik, Wahyuni; Zuliana, Zuliana (Journal of Sustainable Education, 2025)
This research aims to analyze the students' strategies in maintaining a balance between memorizing the Qur'an and general lessons at Madrasah Aliyah Tahfizil Qur'an Medan. This research uses a qualitative approach with the participatory observation method, where the researcher directly observes the daily activities of students, including memorization patterns, learning activities, and interactions in the madrasah environment. The results of the research show that students have a structured daily activity pattern, starting from the morning muraja'ah, general lessons, memorization deposit, until the night muraja'ah. The applied balance strategy includes time management through the preparation of personal schedules and study discipline, energy management by maintaining health and rest, as well as motivational strategies through teacher encouragement, family support, and a religious pesantren environment. This finding is in line with previous research that confirms the importance of tahfiz and general curriculum integration and the role of effective madrasa management. This research concludes that the success of students in maintaining a balance between tahfiz and academics is determined by a combination of internal factors (discipline and self-motivation) and external factors (teacher support, family, and madrasah curriculum policy).